The effect of Merdeka curriculum implementation on students’ English learning motivation and interest - Laili Inayatus Sholihah; Silvia Alfianti Lucky; Nurhaedah Gailea (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Although many researches have examined its application of Merdeka curriculum, Indonesian current curriculum, in teaching practice, little research has examined its psychological impact on students, especially regarding their motivation and interest in learning English. Addressing this gap, this study investigates the impact of the implementation of the Merdeka curriculum on the motivation and interest of grade X students from one of the public high schools in Mancak, Serang, Banten, Indonesia. A quantitative survey research design was used using a structured questionnaire distributed to sixty-two students. The questionnaire consisting of twenty close-ended items was based on a four-point Likert scale to measure student motivation and student learning interest. The data were analyzed using descriptive statistics, including mean, standard deviations, frequencies, and percentages. The results showed that students were highly motivated and interested in learning English through the Merdeka curriculum. Students found learning English enjoyable, meaningful, and relevant to their lives. Future studies should include qualitative methods to gain deeper insights and involve schools from different regions to further validate the findings. This study offers empirical insights for educators and policymakers to improve English language learning by implementing a flexible and student-centered approach under the Merdeka curriculum.